Psychoeducation on Mental Health on the Self-Acceptance of Patients After Schizophrenia Treatment - Alinda, Niken; Safrudin, Muhammad Bachtiar (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Self-acceptance in patients with schizophrenia remains low, as many patients do not fully understand their condition. They often harbor negative prejudices toward others, including family and the community, who tend to stigmatize them. This negative self-stigma leads to low expectations, resulting in diminished self-esteem and self-efficacy, which directly affects the recovery process. This includes reduced self-awareness or insight into the illness, ultimately impacting the quality of life of patients with schizophrenia. This study aimed to determine the effect of psychoeducation about mental health issues on self-acceptance in post-treatment schizophrenia patients in the working area of Wonorejo Public Health Center. The research used a quantitative method with a quasi-experimental design, specifically a pre-test and post-test with a control group. The sampling technique used was random sampling, involving 34 participants-17 in the intervention group and 17 in the control group. Data were collected using a questionnaire and analyzed using univariate and bivariate analysis with paired t-test and Mann-Whitney test. The results showed that psychoeducation had a significant effect on the self-acceptance of post-treatment schizophrenia patients. It is recommended that families provide continuous support and attention to the mental health of schizophrenia patients